Effects of following and opposing vertical current shear on nonlinear wave interactions. (August 2019) - Chen, Haifei; Zou, Qingping
Highlights: OpenFOAM-based numerical depth-varying wave-current flume is validated against analytical solution and experiment. Adding vertical shear to uniform current enhances/weakens harmonic wave energy and triad interaction in following/opposing current. The following current shear may contribute to premature wave breaking at a lower sea state than that with or without uniform current. Wave steepness at which the current shear starts to affect the crest elevation is greater in deeper water than in shallower water. Abstract: A Navier-Stokes solver in OpenFOAM ® is combined with the Volume of Fluid (VOF) surface capturing method to investigate the wave interaction with depth-varying currents in intermediate and shallow waters. A special attention is paid to the separate effect of vertical current shear on near resonant triad wave interactions. It was found that in the presence of following vertical current shear, the wave exhibits a sharper crest and flatter trough, and the opposite is true in the presence of opposing vertical current shear. Our model results indicate that the wave steepness at which the current shear starts to affect the crest elevation is greater in deeper water than in shallower water. We found that adding vertical current shear to the uniform current further enhances the relative harmonic wave energy and the extent of triad interaction in the following current while weakens them in the opposing current. As a result, following and opposing current shear may cause wave to break at a lower and higher sea state respectively. Due to the increased wave nonlinearity in the presence of a following current shear, a linear superposition of the individual wave and current velocities is no longer adequate to represent the total horizontal velocity close to the free surface.